Training on Sustainable Use of Water in the Processing Industry - Moretti, Melita; Markič, Mirko (Naše gospodarstvo/Our economy, 2015)
The aim of this article is to present research results on the influence of factors of sustainable water use training (management support of training, co-worker support of training, incentives for using skills acquired during training) and the influence of this training on technical efficiency and employee efficiency. The article is based on an empirical study of 328 medium and large companies in the Slovene processing industry. The findings show that the training factors have a statistically significant and positive effect on sustainable water use training and that training has a positive effect on technical efficiency. They also offer new theoretical knowledge as well as practical guidelines for anyone working in the sustainable development management of natural resources.